Analisis Dampak Lalu Lintas Pembangunan Perumahan Kirana Garden Residence: Traffic Impact Analysis Kirana Garden Residence Housing Development - Novadli, Azri (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Traffic Impact Analysis (Andalalin) is basically an analysis of the influence of land use development on the surrounding traffic flow system, which is caused by the generation of new traffic, diverted traffic, and by vehicles entering and leaving the development land. The Kirana Garden Residence housing development plan will have an impact on the smoothness of traffic around it, especially the performance of the nearest roads in the development area. Therefore, there is a need for a study to analyze the impacts resulting from the Kirana Garden Residence housing development plan. The aim of this research is to identify the performance of sections and intersections that are estimated to be affected by the Kirana Garden Residence housing construction activities, then formulate efforts to deal with the impact caused by the Kirana Garden Residence housing construction activities on the surrounding traffic. The research method used is the Indonesian Road Capacity Guidelines 2023 (PKJI 2023) approach, with the results namely the value of the degree of saturation of the surrounding road sections and intersections during existing conditions before construction and during operational conditions after the construction of the Kirana Garden Residence housing complex. The results of the research show that there is a decrease in road performance after the Kirana Garden Residence housing development plan, so it is necessary to take action to minimize the impact of traffic that will occur, especially during the Kirana Garden Residence housing construction activities.